How the meaning of lexical units is explained in the Spanish dictionary of the Spanish of Perú (Deper) - Huisa Téllez, José Carlos (2013)
This article develops the fundamental ideas of the Project Diccionario contrastivo del español de América (Contrastive Dictionaries of the Spanish of Latin American), directed by Günther Haensch and Reinhold Werner at the University of Augsburg, Germany, with emphasis on the conception of a differential dictionary and in the way how the corresponding microstructure is organized.